Crustal Contamination Versus Subducted Components: An Example from The West Java Arc, Indonesia and Its implications in Magma Genesis - Mirzam Abdurrachman; Masatsugu Yamamoto (Geological Agency, 2023)
New Sr isotope and K2O data are presented for Papandayan and Cikuray Volcanoes in West Java. The data are combined with published Sr isotope and K2O data, and compared with arc that has a similar geological setting, namely Northeast Japan Arc (NJA, N 38° 41°) to constrain the relative importance of crustal assimilation and subducted input of crustal material in magma genesis beneath West Java Arc (WJA). New strontium isotope and K2O data from fifty-four Quaternary volcanic rocks from WJA were collected and compared to forty-six Quaternary volcanic rocks from NJA. The increasing K2O and decreasing of 87Sr/86Sr ratios with distance from trench have been found in NJA, but there are rough and no across arc variation of K2O and Sr isotopic ratios in WJA. This study shows that the across arc variation of magma chemistry on the WJA is attributed to the crustal assimilation and the involvement of subducted sediments and slab fluids from altered oceanic crust.